2011
DOI: 10.1080/02687038.2011.624584
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of change in the evolution of jargon aphasia

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AcknowledgementsWe thank TK and his family for their participation, patience and support. Funding for this project was received from Bexhill and Rother (NHS) PCT.3 AbstractBackground: The evolution of jargon aphasia may reflect recovery in the speech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The Pick-like possibility of a "two stage error" mechanism for neology suggested that a viable alternative would involve some sort of anomic, and that response Pick suggested was a semantic substitute, which was subsequently altered by phonemic error. This set up a prediction for endstage recovery (Eaton, Marshall & Pring 2011). The conduction theory is not a two stage theory, so recovery from that type of neologism would resolve to correct outputs, or perhaps, this could be the endstage speech output monitoring ability as recently suggested and that was not to be confused with anomia.…”
Section: Neologistic Jargonmentioning
confidence: 94%
“…The Pick-like possibility of a "two stage error" mechanism for neology suggested that a viable alternative would involve some sort of anomic, and that response Pick suggested was a semantic substitute, which was subsequently altered by phonemic error. This set up a prediction for endstage recovery (Eaton, Marshall & Pring 2011). The conduction theory is not a two stage theory, so recovery from that type of neologism would resolve to correct outputs, or perhaps, this could be the endstage speech output monitoring ability as recently suggested and that was not to be confused with anomia.…”
Section: Neologistic Jargonmentioning
confidence: 94%
“…The nonwords are usually phonologically related to the target; however, nonwords with no clear phonological overlap with the target have also been reported (Eaton et al . ). Research investigating naming impairments in jargon aphasia has honed in on a deficit either at the phonological level and/or in accessing the phonological level (e.g., Bose and Buchanan , Hillis et al .…”
Section: Introductionmentioning
confidence: 97%
“…Production in Jargon aphasia is fluent but underspecified and contains numerous non-word errors, rendering it hard to comprehend. Prognosis in Jargon aphasia is poor, with reports of declining vocabulary size and mixed therapeutic outcomes (e.g., Panzeri et al, 1987 ; Robson et al, 1998a , b ; Eaton et al, 2011 ; Bose, 2013 ). Perseveration, repeated patterns of phonological distortion, frequently co-occurs with Jargon aphasia and is particularly evident during elicitation tasks such as serial repetition.…”
Section: Introductionmentioning
confidence: 99%